A new species of Cycloporus from the Adriatic Sea, with an updated phylogeny of the families Euryleptidae and Stylostomidae (Polycladida, Platyhelminthes) - Dittmann, Isabel L.; Grosbusch, Alexandra L.; Bertemes, Philip; Egger, Bernhard (Zootaxa, 2023)
We describe Cycloporus pinkipus sp. n., a new polyclad flatworm species from the Adriatic coast of Croatia using live images, histological sections, and a molecular marker. It is the fifteenth described species of Cycloporus Lang, 1884 and the second described congener in the Mediterranean. The genus Cycloporus is characterised by a small oval body, tentacular bumps and the name-giving marginal pores. Cycloporus pinkipus sp. n. has a smooth dorsal surface, which is transparent creamy white with light brown to yellow spots, covered with prominent serial pink spots on the inner rim of the body margin. There is little variation of the genital organs between different species of the genus, therefore we recognise C. pinkipus sp. n. as a new species in particular due to its unique coloration, and a unique partial large nuclear ribosomal subunit (28S) sequence. In recent years the family Euryleptidae Stimpson, 1857, which also contains the genus Cycloporus, was discussed and revised in several molecular studies. In an updated molecular phylogeny of the Polycladida based on partial 18S and 28S rDNA marker genes, C. pinkipus sp. n. was recovered in a clade of many other Cycloporus species within Euryleptidae.